Iowa Birdline update, January 9, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for January 9, 1995. Highlights include Varied Thrush, Gyrfalcon and Bohemian Waxwing. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed